The Influence of Leadership Style and Competence on Employee Performance with Work Motivation as a Mediating Variable at PT Sembilan Dimensi Jakarta - Abdul Kodir Djaelani; Imam Muhtadin; M. Yusuf (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine and examine the effects of leadership style and competence on employee performance, considering the mediating role of work motivation at PT. Sembilan Dimensi Jakarta. The research employs an associative method with a quantitative approach. The sample includes 50 respondents, all employees of PT. Sembilan Dimensi Jakarta, using a saturated sampling technique since the entire population was surveyed. Data analysis was performed using the SEM-PLS method. The findings indicate that (a) leadership style does not influence employee work motivation, (b) competence significantly influences employee work motivation, (c) leadership style significantly affects employee performance, (d) competence does not impact employee performance, (e) work motivation significantly influences employee performance, (f) leadership style does not affect employee performance through work motivation, and (g) competence does not impact employee performance through work motivation. The conclusion of this study is that work motivation plays a crucial role in the relationship between competence and employee performance, but not in the relationship between leadership style and employee performance